HUBUNGAN MOTIVASI KERJA DENGAN BUDAYA ORGANISASI KARYAWAN PADA DIAN KONVEKSI BANDUNG - Andri Irawan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Working world to day face a highly competitive situation including small and mediumenterprises. the biggest disadvantage of small and medium enterprise sector is the skills of itshuman resources. A good working environ mentis expected by employees in maintaining hismotivation to always remain high this so that the employees are always able to face the challengesof higher organizationAssociative method in this study is used to find how much the relation ship between workmotivation and organizational culture on Dian Convection. The population in this study wereemployees at Dian Convection, amounting to 10 people. Types of statistics used are parametricstatistical correlation analysisCorrelation coefficient of 0.940 interpret that relation ship work motivation and organizationalculture on Dian very strong. This is because there is a strong emotional connection in the form of along friendship and positive among employees Dian Convection